Vulnerability of medical students and professionals to extreme work stress: A select review of the literature. (29th May 2017) - Walkiewicz, Maciej; Tartas, Małgorzata
Abstract : The goal of the paper is to describe the extent to which medical students and professionals are vulnerable to extreme stress. A select review of existing literature on this area has been undertaken, using the English-language online databases EBSCO, Medline and PubMed. The search has identified 36 citations relating to 6324 medical students and 28, 285 medical staff (physicians, residents, nurses). The review indicates that merely beginning medical studies is a risk factor for stress, and that medical professionals, who are vulnerable to extreme work stress, say that they do not receive enough support from their co-workers. They are also often notably impulsive, introverted, neurotic and perfectionist, with low emotional intelligence and agreeableness, as well as low and external locus of control. Additionally, from longitudinal studies we have been able to identify psychological factors underpinning admission to a medical university that may be useful for predicting future stress in medical career. The results of this study may be taken into account when organizing psychological intervention programs targeted at educating future medical professionals. It seems that early identification of people at risk could reduce the impact of stress related to medical career and enhance the somatic and mental health of medical professionals.